2020
DOI: 10.1186/s12891-020-03845-7
|View full text |Cite
|
Sign up to set email alerts
|

Translation step-cut osteotomy for posttraumatic Cubitus Varus in adults: a retrospective study

Abstract: Background Cubitus varus is a complex three-dimensional deformity. Various osteotomies have been introduced to correct this complex deformity. The objective of the present study was to evaluate clinical and functional outcomes of adult cubitus varus deformity treated with translation step-cut osteotomy. Methods Seventeen consecutive patients with a mean age of 25 years (range, 19–50 years) who underwent translation step-cut osteotomy were enrolled in this study. Their average follow-up period was 28.2 months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Although the cause of varus deformity remains uncertain, many authors believe that angular and rotational deformities are causes of varus deforimity. 18) de Gheldere and Bellan 19) have reported that laterally torn periosteum is associated with posteromedially displaced fractures, whereas medial periosteal rupture is associated with posterolateral displaced fractures, providing a higher Baumann value inducing cubitus varus deformity in the posteromedially displaced type. Small distal bone fragments might cause varus deformity by making accurate closed reduction difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cause of varus deformity remains uncertain, many authors believe that angular and rotational deformities are causes of varus deforimity. 18) de Gheldere and Bellan 19) have reported that laterally torn periosteum is associated with posteromedially displaced fractures, whereas medial periosteal rupture is associated with posterolateral displaced fractures, providing a higher Baumann value inducing cubitus varus deformity in the posteromedially displaced type. Small distal bone fragments might cause varus deformity by making accurate closed reduction difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In children, the most common reason for surgery for cubitus varus is cosmetic deformity [2]. In adults, surgery has been considered when symptomatic conditions such as PLRI or ulnar nerve symptoms become apparent [1,[3][4][5] or when there is a cosmetic problem [6].…”
Section: Introductionmentioning
confidence: 99%
“…[5] The currently used osteotomies include lateral closed wedge osteotomy, [6] medial open wedge osteotomy, step-cut osteotomy, and dome-shaped osteotomy. [7] At present, lateral closed wedge osteotomy is the simplest and most commonly used osteotomy method in clinical practice. However, this method leads to an inconsistent diameter of the proximal and distal ends of the osteotomy and results in obvious deformity of the distal humerus, which is manifested by the appearance of the steps of the distal humerus on imaging.…”
Section: Introductionmentioning
confidence: 99%